PENGARUH BEBAS-HUJAN SETELAH APLIKASI TERHADAP EFIKASI GLIFOSAT PADA GULMA DI LAHAN KELAPA SAWIT - Riwandi Aritonang (Institute of Computer Science (IOCS), 2021)
The objective of this research was to study the efficacy of herbicide products with active ingredients of glyphosate on some rain-free period after application to weeds in oil palm plantations. The research were are design arranged in split-plot design with two factors and three replications. The main factor is glyphosate herbicide (Crucial 700; Crucial 550; Roundup Power Max; Roundup Biosorb; Kleenup). And the second factor is period rain-free after aplications (0.5; 1.0; 2.0; 4,0; and no rain). The results of this study showed that all glyphosate-based herbicides required rain-free period after application more than where the efficacy four hours. The highest damage (80 %) of weed on rain free time after 12 hours.